Geomorphological Insights on Human-Volcano Interactions and Use of Volcanic Materials in Pre-Hispanic Cultures of Costa Rica through the Holocene - Ruiz, Paulo; Mana, Sara; Gutiérrez, Amalia; Alarcón, Gerardo; Garro, José; Soto, Gerardo J. (Frontiers in Earth Science, 2018)
Critical Zones in tropical environments, especially near active volcanoes, are rich in resources such as water, food and construction materials. In Central America, people have lived near volcanic centers for thousands of years and learned to take advantage of these resources. Understanding how pre-Hispanic societies lived in this type of Critical Zones and interacted with volcanoes, provides us with insights on how to reduce the negative impact derived from volcanic activity in modern cities. In this multidisciplinary approach we focus on two case studies in Costa Rica near Poás and Turrialba volcanoes, which are currently active, in order to obtain a comprehensive view of human-volcano interactions through time. We use a methodology based on historical accounts, geological and archaeological fieldwork, geomorphological characterization based on remote sensing techniques and past (pre-Hispanic), and present land use analysis. The northern Poás region represents a case of a poorly developed pre-Hispanic society, which subsisted mainly on hunting and gathering activities, had no permanent settlements and was probably affected by the activity of the Hule and Río Cuarto maars. In spite of their vulnerability and lack of infrastructure, they used geomorphology to their advantage, achieving natural protection. Conversely, the Guayabo National Monument near Turrialba Volcano represents a cultural peak in pre-Hispanic societies in Costa Rica. Archaeological remains and structures at this site indicate that this society had a good understanding of physical and geological processes and was therefore able to take advantage of natural resources for water and food supply, construction, and protection as well as hazard prevention and mitigation. The use of new technologies, some accessible and low-cost such as Google Earth and others with restricted access and higher costs such as LiDAR, allowed us to complete a rapid and efficient characterization of land use and geomorphological features of the study area. This study helps to establish how some locations near volcanic edifices are more prone the effects of volcanic hazards than others and why this data should be included in volcanic risk assessment and land planning processes.